MURTAD: ANTARA HUKUMAN MATI DAN KEBEBASAN BERAGAMA - Abd. Rahman Dahlan (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2010)
One of controversial issues emerged in this country dealing with ethnicity, religion, and race lately is the issue of apostasy and the punishment for the converts. Dealing with this, the religious persons are polarized into two groups; the first group helds the majority opinion of fiqh ulama that the punishment for the coverts is the death sentence. The second one argues that they are merely judged as laden with sin, not a crime case. This article tries to analyze both two views by using hadits approach. Keywords: apostasy, riddah mugha / ladzah, riddah mukhajfafah, capital punishment